Pengaruh kinerja guru terhadap pemahaman siswa - Tikasari, Putri Ariyatna (Maliki Interdisciplinary Journal, 2025)
In the world of education, students understanding of the subject matter can also be influenced by several key factors, one of which is the performance of the teacher. Effective teaching methods to enhance students understanding and learning motivation need to be implemented through qualified and professional teachers. This article aims to demonstrate how teacher performance can influence student understanding, with an emphasis on teacher quality, teacher qualifications and training, as well as teaching methods and srtategies. The research results show that good teacher performance, characterized by teacher qualifications, as well as various teaching methods and strategies, can enhance student motivation and understanding. In addition, periodic learning evaluations are also necessary to ensure that the learning process runs smoothly. As a result, improving the quality of teachers through continuous training is very important to achieve optimal learning outcomes.